A REVIEW OF ANTENNA DESIGN OPTIMIZATION FOR PARTIAL DISCHARGE DETECTION IN HIGH VOLTAGE EQUIPMENT - Mukhtar Hadi; Kodrat, Muhammad; Oktavia, Siska Atmawan (TESLA: Jurnal Teknik Elektro, 2025)
Partial discharge (PD) is a critical indicator of insulation degradation in high-voltage equipment such as power cables, transformers, and joints. Undetected PD activity can accelerate insulation failure and cause system breakdowns. Among various detection approaches, antenna-based electromagnetic sensing offers significant advantages due to its non-intrusive nature and ability to detect radiated PD signals remotely. This paper presents a comprehensive review of antenna designs developed for PD detection between 2013 and 2023. A total of 67 antenna models from 22 researchers were analyzed, encompassing 182 simulation and measurement data points that include return loss (RL), voltage standing wave ratio (VSWR), and bandwidth (BW). The findings reveal that Bowtie and Microstrip antennas dominate PD detection research due to their wide bandwidth and compact form. Performance trends indicate significant improvement, with RL values reaching –30 dB, VSWR decreasing to below 1.3, and bandwidth exceeding 3 GHz. The study identifies four major innovation phases, transitioning from basic geometry optimization to multi-layer and hybrid adaptive designs. Recommendations for future research include hybrid bowtie–Microstrip configurations, the use of flexible or low-loss substrates, and integration with intelligent signal processing and machine learning systems. These advancements are expected to support the development of next-generation smart PD detection systems with high sensitivity and efficiency Abstrak Partial discharge (PD) merupakan indikator utama degradasi isolasi pada peralatan tegangan tinggi seperti kabel daya, transformator, dan sambungan (joint). Aktivitas PD yang tidak terdeteksi dapat mempercepat kerusakan isolasi dan menyebabkan gangguan sistem. Di antara berbagai metode deteksi, pendekatan berbasis antena memiliki keunggulan karena bersifat non-intrusif dan mampu mendeteksi sinyal elektromagnetik PD dari jarak jauh. Artikel ini menyajikan kajian komprehensif terhadap desain antena untuk deteksi PD selama periode 2013–2023. Sebanyak 67 model antena dari 22 peneliti dianalisis, meliputi 182 data hasil simulasi dan pengukuran dengan parameter return loss (RL), voltage standing wave ratio (VSWR), dan bandwidth (BW). Hasil menunjukkan bahwa antena Bowtie dan Microstrip mendominasi karena memiliki lebar pita yang luas dan bentuk yang kompak. Tren performa memperlihatkan peningkatan signifikan, dengan nilai RL mencapai –30 dB, VSWR menurun hingga <1,3, dan bandwidth melebihi 3 GHz. Kajian ini mengidentifikasi empat fase inovasi utama, dari optimasi bentuk dasar hingga desain multi-layer dan hybrid adaptif. Rekomendasi pengembangan ke depan meliputi desain hibrid Bowtie–Microstrip, penggunaan substrat fleksibel atau ber-loss rendah, serta integrasi dengan sistem pemrosesan sinyal dan mechine learning. Inovasi ini diharapkan mendukung pengembangan sistem deteksi PD cerdas generasi berikutnya yang lebih sensitif dan efisien